Forward/Backward Decomposition for Dispersive Wave Propagation Measurements - Nicholas A. Corbin; Pablo Tarazaga (Applied Sciences)
Two complicating features commonly found in wave propagation applications include dispersion, i.e., frequency-dependent propagation velocity, and reflections, which introduce coherent noise. In this work, we present a signal processing technique which can be applied in a variety of applications to decompose signals into their forward- and backward-propagating components. The theory is presented, along with algorithmic implementation and experimental validation on a Timoshenko beam. The implications and potential utility of the method are briefly discussed.